RASIO HUTANG SERTA PERPUTARAN MODAL KERJA DAN PENGARUHNYA TERHADAP PROFITABILITAS PERUSAHAAN - Linna Ismawati; Melani Karlina (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
AbstractThe assurance includes the business that strictly regulated by government with the purpose to protect consumer from an underhand way of doing by enterprise. There is capital ratio margin through collected premium caused several assurances to measure and compare their performance with effective in order to hold out and competitive in business world. Assurance enterprise always evaluates their operational as long as year with identifying various internal and external factors which can influence profitability.This study uses descriptive and verificative methods. The sample in this study amounts 20 data that taken by purposive sampling technique. Collecting data uses documentation, library research, and internet research, in data managing uses regression linear analysis, analysis castellation Pearson, determination, f-test and t-test, statistic data managing uses program addition such as Excel and SPSS 20 For Windows.The study result shows that Work Capital and Debt Ratio Turnover has strong relationship through profitability. And it has influence as big as 8.40%. Then from such study result, partially correlation for work capital turnover with profitability, positive, then positive correlation value shows the relationship between revert variable. Where, if more and more small or decrease work capital turnover value, resulted profitability more and more large or high or obtained the number of profit. So that debt ratio has influence as big as 7.78%. Furthermore from computation result determination coefficient with contribution as big as 70% while reminder 30% are influenced by other factors such as storage, fixed asset, trade cost (general & administration costs, and other costs).Keywords: Work Capital Turnover Debt Ratio, Profitability